360° Video: Interview with Claudia Parducci, artist, Los Angeles, 16 September 2017 - Messham-Muir, Kit (StudioCrasher, 2017)
This is the second half of a two-part interview with Claudia, a Los Angeles-based contemporary artist. Since our first interview in 2012, I've interviewed Claudia several times, and her practice is currently the focus of a more in-depth research project looking into studio practice today. In this two-part 360° interview, Claudia talks about her more recent work and the newly-charged context of Trump's America.